Summer reading is killing me! - Scieszka, Jon.; Smith, Lane (New York : Viking, 1998)
At the beginning of summer vacation Joe, Sam, and Fred find themselves trapped inside their summer reading list, involved in a battle between good and evil characters from well-known children's books.
4.8
3-6
3-6
Wilson's Children
Elem. School Library Collection
School Library Journal starred
Keywords: Books and reading -- Fiction; Characters in literature -- Fiction; Magic -- Fiction; Books and reading -- Fiction; Characters and characteristics in literature -- Fiction; Magic -- Fiction